Characterization of the current cleaning practices of milk cooling tanks in the brazilian semi-arid region (Research, Society and Development, 2021)
Milk is a highly perishable food and its quality is essential for human consumption. Therefore, the dairy farm must employ processes for cooling milk and cleaning equipment in order to preserve the quality of the product. The objective of this study was to characterize the knowledge of the person responsible for good practices for cleaning the milk cooling tank, and to evaluate the hygiene of this equipment used in dairy farms in the semiarid region of Rio Grande do Norte-RN. A questionnaire was applied in 27 dairy farms distributed in 14 municipalities in the state to collect data on the knowledge of the person responsible and the cleaning of the tanks. Qualitative and quantitative data were analyzed by calculating means and standard deviations and differences were obtained using Duncan's test. Among the 27 tanks, 50% had a cleaning score of 3 (poor), 33.3% good and 16.67% very good. About the knowledge of cleaning the tanks, 51.86% of the producers had very good or good knowledge, and 48.15% had bad knowledge. Only 25.93% of owners use sanitation methods. This work can constitute a technical reference, serving as a subsidy to evaluate the environmental and financial impacts in the execution of the cleaning of equipment in milk production.